(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Separation from circulation of units of money is demonetization units of money are refused legal tender status. Demonetization is characterized as a mechanism in which monetary units are not lawfully tendered. The money notes are not known to be true currencies. Demonetization is a government measure under which currency units are no longer valid. Demonetization is a necessary prerequisite for replacing the national currency. In other terms, demonetization is a currency reform in which new currency units substitute the existing currency. That may entail the release of new notes or coins of the same name or different name. The money in India was demonetized three times. The first was demonetized on 12 January 1946 (Saturday), the second was demonetized on 16 January 1978 (Monday) and the third was on 8 November 2016 (Tuesday). The research aims at explaining the importance and explanations for demonetization, the sectoral effect of demonetization. This analysis offers also a summary of the positive and negative influence of demonetization on the Indian economy. This research is comprehensive and has taken all the necessary and applicable data from different papers, journals and websites. Books were also referred as needed for theoretical knowledge on the subject.